Faktor-faktor yang mempengaruhi keberkesanan pemindahan latihan komputer di Telekom Malaysia berhad, Kuching - Kuo, Poh Shin. (Universiti Malaysia Sarawak (UNIMAS), 2005)
This study aims at identifying the various/actors (gender, age, educational/eve/, trainee motivation, training content, supervisoly SUppOrL. opportunity to apply, rewards system, memory, and self-efficacy) aJJecting the effectiveness o( rraining transfer 0/computer-based skills training ar Telekoln Malaysia Berhad. Kuching. Questionnaires were used to obtain feedback frO In 56 rcspondenr.l· who had attended the computer training between JanuQly to June 2004. The data collected was analyzed by using the Statistical Package /01' the Social Sciences (SPSS) , Version 12. O. The result of T-test analysis showed [hat there was no significan[ difference between demographic variables (gender and educational level) and effectiveness 0/ transfer 0/ training. Analysis by using ANOVA test showed [hat there was no significant difference between age and effectiveness o( tran.y(er o( training. The .finding o( Pearson Correlation showed that there arc significant relationships between the /actors studied and the effectiveness of transfer of training. These factors are trainee motivation. training content, supervisory support, opportunity to apply, rewards system. memory, and sel(-efficacy. Multiple Regression Analysis showed that among the seven /acrors, sel(-efficacy plays a dominant role in influencing the effectiveness o( transfer o( training. As a cone/us ion, trainee motivation, training content. supervisory support. opportunity to apply, rewards system. memory, and self efficacy do influence effectiveness l?f transfer 0/ computer training in Telekom. implication o( this study can help Telekom ensure the positive transfer 0/ training being conducted. As a result, management an.d trainers would obtain benifits/rom computer-based training.